PERUBAHAN BENTUK FISIK BALE WANTILAN SEBAGAI FUNGSIPENUNJANG KOMPLEK PARAHYANGAN - I Kadek Arya Adi Wirawan; Bagus Made Arjana; Desak Made Sukma Widiyani (Jurnal Anala, 2016)
Bale Wantilan is a building that is open in all directions without being limited wall that has a roof bertumpang. Bale Wantilan referred to in this study is Bale wantilan who are still using the original patterns of traditional Balinese architecture. That is built on the principles enshrined in the palm and palm Asta Asta Kosala Kosali Bhumi. Generally set up Bale wantilan during set up and after the establishment of complete, followed by the process steps in line with the ceremonial work steps. After building completion ceremony "melaspas" and "Mendem Pedagingan" the largest in a series of other ceremonies. In subsequent ceremonies when the building suffered natural disasters or manmade disasters, buildings and grounds area was cleared wantilan Bale back in ritual after being repaired as necessary.This study aims to understand the changes in Bale wantilan, to find a clearer picture of the changes that occur in Bale wantilan complex "Parahyangan". Data collection methods used by survey method, ie, with survey data collection directly in the temple area, library research from various sources readings. Data collection techniques using observation and interviews. The results of this study showed that for any changes-changes that occur in Bale wantilan this is no longer a building that is open in all directions. This is due to the use of the walls of a room divider as a result of the demand for space requirements therein. In addition, the function of the complex parahyangan Bale wantilan today not only as a place to support kegiataan religious ceremonies, but rather as a place for meetings, staging and sometimes functioned as a place to carry out the ceremony "Tabuh Rah". Bale shape Wantilan in complex parahyangan from time to time has undergone many changes, no longer square, but today many Bale wantilan rectangular. It, too, due to the demands of space. Ornaments that are adapted to the culture and the culture of the local environment, such as the joints decoration, pillars (columns), listplank, pemade etc. The use of materials and ornaments on Bale wantilan now starting to be simplifiedKeywords: Traditional architecture of Bali, Bale Wantilan, Changes